Penggunaan Stetoskop Elektronik pada Kelainan Katup Jantung - Mangole, Josua Edison; Nurachmah, Elly; Waluyo, Agung; Adam, Muhamad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to see the effectiveness of using an electronic stethoscope compared to a conventional one in patients with heart valve disorders. The method used in this writing is a systematic review through several databases, namely Pubmed, ClinicalKey, Proquest, Science Direct, and Scopus. The article analysis process uses the PRISMA method. The research results show that electronic stethoscopes are more expensive because many parts and applications/software are added. Still, they are very efficient in accurately diagnosing specific heart sound abnormalities and have more advantages than conventional stethoscopes. In conclusion, electronic stethoscopes are very effective and efficient in increasing the speed and accuracy of diagnosing specific heart sound abnormalities, so they have more benefits. Keywords: Heart Valves, Electronic Stethoscope